Occupational Happiness of Civilian Nurses in China: a cross-sectional study - Ying Meng; Xue Luo; Peng Sun; Yu Luo; Zonghua Wang; Lihua Wang; Yuhong Ge; Li Lin (BMC, 2023)
Abstract Background Civilian nurses have gradually become the main body of military nurses. Our study aimed to understand their occupational happiness and its influencing factors. Methods This descriptive study was conducted with 319 civilian nurses working in 15 military hospitals in China. Based on literature review, expert consultation and combined with the characteristics of civilian positions, this study developed a questionnaire on occupational happiness of civilian nurses in military hospitals. The questionnaire includes 7 dimensions as follows: work emotion, salary, work environment, professional identity, work output, interpersonal relationship, well‑being. The demographic questionnaire and occupational well-being questionnaire of civilian nurses in military hospitals were analysed by t-test, analysis of variance and Pearson correlation analysis. Results The occupational happiness score (3.83 ± 0.56, upper limit score: 5) was at the upper middle level. There were significant differences in occupational well-being by gender (t = -2.668, p = 0.008), age (F = 5.085, p = 0.007) and the type of city where the hospital was located (F = 15.959, p < 0.0001). The happiness score of females (3.94 ± 0.60) was higher than that of males (3.47 ± 0.54). Nurses who were over 41 years old had the highest occupational happiness. Compared with nurses younger than 30 years old, the p value was 0.004. The occupational happiness of nurses in hospitals in a "prefecture-level city" (p < 0.0001) and a "sub-provincial city" (p < 0.0001) was significantly higher than that of nurses in hospitals in a "municipality directly under the central government". Correlation analysis showed that the higher the nurses' satisfaction with professional identity, work output, work environment, salary, and interpersonal relationships, the higher their occupational happiness. Conclusion Occupational happiness of civilian nurses in Chinese military hospitals was above the medium level. Gender, age, and the type of city where the hospital was located had a very significant impact on the level of occupational happiness. In addition, "professional identity", "work output", "work environment", "salary", and "interpersonal relationships" were significantly correlated with the occupational happiness of civilian nurses. They can be improved with some future lines of research.